2007
DOI: 10.1073/pnas.0700365104
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the Mozambique strain of Vibrio cholerae O1 reveals the origin of El Tor strains carrying classical CTX prophage

Abstract: Cholera outbreaks in subSaharan African countries are caused by strains of the El Tor biotype of toxigenic Vibrio cholerae O1. The El Tor biotype is the causative agent of the current seventh cholera pandemic, whereas the classical biotype, which was associated with the sixth pandemic, is now extinct. Besides other genetic differences the CTX prophages encoding cholera toxin in the two biotypes of V. cholerae O1 have distinct repressor (rstR) genes. However, recent incidences of cholera in Mozambique were caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 34 publications
3
68
0
1
Order By: Relevance
“…Interestingly, a sharp genetic transition of V. cholerae from the ET Mozambique variant to the Asian altered ET (possessing ctxB of the CL biotype) was observed in north-east Thailand in 2007, with all of the tested V. cholerae strains acquiring RS1 and TLC and switching the repressor rstR allele from rstR CL (CL) to rstR ET (ET), as in the altered ET reported from Bangladesh (Nair et al, 2006) and India (Raychoudhuri et al, 2008). Our data on the temporal absence of virulence and related genetic elements and their acquisitions clearly indicate horizontal gene transfer, which has been proposed to provide V. cholerae strains with improved evolutionary fitness (Faruque et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Interestingly, a sharp genetic transition of V. cholerae from the ET Mozambique variant to the Asian altered ET (possessing ctxB of the CL biotype) was observed in north-east Thailand in 2007, with all of the tested V. cholerae strains acquiring RS1 and TLC and switching the repressor rstR allele from rstR CL (CL) to rstR ET (ET), as in the altered ET reported from Bangladesh (Nair et al, 2006) and India (Raychoudhuri et al, 2008). Our data on the temporal absence of virulence and related genetic elements and their acquisitions clearly indicate horizontal gene transfer, which has been proposed to provide V. cholerae strains with improved evolutionary fitness (Faruque et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
“…However, the tcpA gene of V. cholerae O1 ET strains isolated in 2007 and thereafter had a mutation at amino acid position 64 (NAS). Although the change is subtle and it is not clear whether such genetic switching of the tcpA gene can provide V. cholerae O1 strains with increased environmental and/or epidemiological fitness (Faruque et al, 2007), a similar change of amino acid at position 64 of TcpA was found in ctx 2 V. cholerae O1 strains ZJ65 (2006) isolated in China (GenBank accession no. EU622532) and V. cholerae strain 2010EL1786 (GenBank accession no.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of the mechanism of integration of the classical variant of CTXϕ were complicated because no phage production was observed in any of the strains harboring it (3,11). To circumvent this difficulty, we used conjugation to deliver circular DNA molecules carrying the replication and integration region of the phage found in the 569B classical strain, hereafter referred to as "RS Cl ," directly into V. cholerae cells.…”
Section: The Variant Of Ctxϕ Found In the 569b Classical Strain Integmentioning
confidence: 99%
“…1C). Nevertheless, the classical variant of CTXϕ was found integrated at dif2 in classical strains (3) and in recent El Tor isolates (4,(10)(11)(12)(13)(14). The mode of dissemination of this variant is of particular interest, because it allows the production of an elevated amount of cholera toxin (15,16) that seems to be implicated in a high proportion of severe infections associated with classical strains (17).…”
mentioning
confidence: 99%